Bending of optical solitonic beams modeled by coupled KMN equation. (1st October 2022) - Mukherjee, Abhik
Abstract: The dynamics of (2 + 1) dimensional optical solitonic beams modeled by coupled Kundu Mukherjee Naskar (KMN) equation are discussed by deriving one bright and one dark soliton solution. The arbitrary bending of solitonic beams of this coupled system has been described by exact curved soliton solutions having an arbitrary function. Such exact analytical results on the bending of solitonic pulse in a bimodal optical fiber system may pave new research directions in this field.